2020
DOI: 10.5858/arpa.2020-0058-ra
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Neoplasia in the Esophagus

Abstract: Context.— Squamous lesions of the esophagus encompass a spectrum of disorders ranging from reactive changes and benign papilloma to squamous dysplasia and squamous cell carcinoma, which may pose diagnostic challenges especially in superficial biopsies. Objective.— To provide a review on the typical features of squamous neoplasia in the esophagus, with an emphasis on the key diagnostic features as well as differential diagnosis from mimicking lesions. Data Sources.— Data sources include published peer-reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Vienna classification 1 (Figure 2 and 3). papillary leukoplakia), their therapeutic alternatives are: resection with biopsy, cauterization, radiofrequency ablation, mucosectomy for large lesions and esophagectomy if the presentation is extreme and does not respond to more conservative therapy [6]. In this case, the lesion was single and small, which corresponds to what is described in the literature.…”
Section: Figures 1-3 Show the Results Of Macroscopic And Microscopic ...supporting
confidence: 60%
See 1 more Smart Citation
“…Vienna classification 1 (Figure 2 and 3). papillary leukoplakia), their therapeutic alternatives are: resection with biopsy, cauterization, radiofrequency ablation, mucosectomy for large lesions and esophagectomy if the presentation is extreme and does not respond to more conservative therapy [6]. In this case, the lesion was single and small, which corresponds to what is described in the literature.…”
Section: Figures 1-3 Show the Results Of Macroscopic And Microscopic ...supporting
confidence: 60%
“…Human papillomavirus infection has been related to the development of squamous cell carcinomas in the anogenital, oral, and laryngeal regions; the prevalence of dysplastic lesions of the hypopharynx ranges between 13% and 24% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, squamous papillomas consist of a papillary proliferation of non-dysplastic squamous epithelium with fibrovascular cores of lamina propia and koilocytes can be seen; progression to dysplasia or carcinoma is extremely rare. 8 Infection with HPV has been found in apparently normal oesophageal mucosa, squamous papillomas and squamous cell carcinomas of the oesophagus. It has been suggested that HPV has a role in the pathogenesis of squamous cell carcinoma of the oesophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the authors collected the histologically confirmed images from consecutive patients with any type of esophageal cancer or precursor lesions found during upper gastrointestinal endoscopy to reflect a real situation. Various prevalence values of squamous dysplasia ranging from 3% to 38% have been reported in the literature [ 17 , 18 ]. , However, a small distribution (1.3%) of esophageal dysplasia was noted in the training dataset in our study.…”
Section: Discussionmentioning
confidence: 99%